Prevention And First Aid of Mechanical Airway Obstruction Among Children: Supportive Stratiges For Mothers - Nadia Abdel-Latif Ali1 , Huda Shawky Mahmud2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Children considered as one third of today’s population and the whole future for us. For raising societybeing healthy, it is vital of having children being healthy. Mechanical airway obstruction is a communaland fatal fortune in group of pediatric age. It needs prompt treatment and recognition for avoiding outcomesas fatal. Despite aspiration of foreign body (FBA) could be event as threatening of life, it can be stillpreventable. The mostly significant risk factor for FBA is caregivers knowledge lacking. A pre/post quasidesign of experimental was implemented in the outgoing study. Three hundred mothers as purposive wereincluded in the current study. The study aim was to assess the supportive strategies influence for mothersin respect to prevention and first aid of mechanical airway obstruction among children. The work wasperformed in the outpatient pediatric department of El Sayed Galal University hospital. Tool I: data sheetas socio-demographic for children and their mothers, Tool II and Tool III: sheet of questionnaire in respectto knowledge of mothers besides reported practices of mothers. Results showed that the mean age of thestudied mothers was (34.13± 8. 97), and more than three quarters of them (%76.7) were didn’t receiveprevious training program. Differences of significant were detected between post and pre supportive strategyin knowledge of mothers and reporting practices in prevention and first aid of chocking that wasn’t affectedby their socio-demographic characteristics (P value ?0. 05).